2018
DOI: 10.1149/2.0311815jes
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Ag Rich Pd-Ag Bimetallic Electrocatalyst for Ethylene Glycol Oxidation in Alkaline Media

Abstract: Efficient electrocatalysts at decreasing cost for ethylene glycol (EG) oxidation reaction are highly demanded for generating electricity out of direct EG fuel cells and producing hydrogen from EG electroreforming cells. In this work, carbon-supported Pd-Ag bimetallic catalysts (Pd x Ag y /C) with varying atomic ratios (x: y = 2: 1, 1: 1, 1: 2, 1: 3 and 1: 4) are synthesized by adding a Pd(II) precursor solution in a preformed Ag colloid in the presence of ascorbic acid followed by mixing with carbon black, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…1d ) peak positions, however, vary only by a maximum of ~−0.3 eV. This small shift is in qualitative agreement with the majority of previously reported Pd 3 d BE shifts in Ag-Pd alloys (mostly negative BE shifts); 21 , 26 , 28 , 32 however, owing to instrument energy resolution it is difficult to draw trends as a function of Ag composition.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1d ) peak positions, however, vary only by a maximum of ~−0.3 eV. This small shift is in qualitative agreement with the majority of previously reported Pd 3 d BE shifts in Ag-Pd alloys (mostly negative BE shifts); 21 , 26 , 28 , 32 however, owing to instrument energy resolution it is difficult to draw trends as a function of Ag composition.…”
Section: Resultssupporting
confidence: 90%
“…This negative shift in the Ag 3 d doublet, as a function of Pd content, has been seen previously for mixed Ag-Pd systems 21 , 26 and has been attributed to increased charge mixing. Specifically, studies have shown that with increasing Pd content, the electron density in the Ag d -band increases, whereas the electron density in the sp -band decreases 21 , 28 , 32 . The Pd 3 d (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A strong reduction peak at À 0.4 V is attributed to the reduction of PdO to Pd. [55] We have also found a small oxidation peak around À 0.2 V for the Pd/GCE-0.1 V_400S in 1 M KOH having no AA (see Figure 2a cyan line). This oxidation peak is due to the development of Pd 2 + from Pd 0 in alkaline conditions.…”
Section: Electrocatalytic Activitymentioning
confidence: 60%
“…Alkaline conditions as well as a high temperature are very aggressive to PdCo-Ni foam catalysts, for which the authors introduced an external layer of phosphates to prevent Pd dissolution and resulted in stable current density up to 10 h. [261] Similar stabilizing strategy with P has also been reported with graphene-supported PdP 2 nanocrystals where P could modify the electronic structure of Pd and Pd-rich surface and improve the charge-transfer kinetics as well as the stability. [262] The electrochemical reforming reactions of diols and polyalcohols, such as ethylene glycol, [267][268][269] 1,3-propanediol [270] have also been reported over the last decade, which all have shown promising performances toward H 2 production with reduced electricity consumption. The reaction parameters for general alcohol electro-reforming are summarized in Figure 20.…”
Section: Ethanolmentioning
confidence: 99%